Comparison of the effects of ispaghula and wheat bran on rat caecal and colonic fermentation. Issue 9 (September 1992) - Edwards, C A; Eastwood, M A
Abstract : The effects of ispaghula and wheat bran on the contents of the caecum and proximal and distal colon of the rat were investigated to identify any differences that might account for their effects on colonic motility. Rats fed diets supplemented with 5% ispaghula and 10% wheat bran for 28 days were killed and the contents of the gut collected. Caecal and colonic content wet and dry weight and short chain fatty acid (SCFA) content were measured. In additional in vitro fermentations in batch cultures of mixed rat caecal bacteria with ispaghula and bran, SCFA production was monitored over 24 hours. Both ispaghula and wheat bran increased faecal weight but ispaghula was more effective. Ispaghula resulted in greater and more liquid contents, with a characteristic pattern of SCFA production (higher propionic acid) maintained throughout the colon. In contrast, wheat bran affected only the caecum and faeces. SCFA content and wet and dry weight in the proximal and distal colon were unaffected by wheat bran. Caecal butyrate was characteristically higher in wheat bran fed rats but ispaghula produced higher butyrate in the distal colon. In contrast, ispaghula seemed to be fermented more quickly in vitro than wheat bran. Thus, wheat bran has a portion that is rapidly fermented and an inert residue that may stimulate motility. Ispaghula seems to be fermented throughout the colon but maintains a high water content which dilutes the luminal contents.